Family-based substance use screening and intervention for adolescents with chronic medical conditions: a study protocol to implement SBIRT-family within school-based health centers - Summersett Williams, Faith; Larez, Natalie A.; Mondesir, Lauren; Curtis, Kennedy; Valdivia, Sara; Becker, Sara; Papineau, Kenneth; Hogue, Aaron (Frontiers in Health Services, 2025)
BackgroundAdolescents with a chronic medical condition (CMC) have an increased risk of developing a substance use (SU) disorder, despite the impact that SU may have on disease-related outcomes. School-based health centers (SBHCs) offer universal screening, brief intervention, and referral for adolescents with chronic medical conditions for substance use treatment. Screening, Brief Intervention, and Referral to Treatment (SBIRT) is an evidence-based early intervention used to detect and address risky substance use that has yet to be broadly adopted in public schools. Moreover, despite extensive research supporting caregiver involvement in treatment for adolescent substance use, SBIRT models that actively engage caregivers are lacking. The primary goal of this qualitative study is the identification of contextual determinants (e.g., barriers and facilitators) of SBHCs implementation potential and adaptation needs of a family-based SBIRT protocol for integration into SBHCs.MethodsWe are conducting this study in two SBHCs within the Chicago Public School system. In these SBHCS we are conducting focus groups with school partners (∼ 30 SBHC staff,∼25 adolescents with chronic medical conditions, and∼25 caregivers). Focus groups will be audio recorded and conducted in English. The semi-structured focus group guides were designed based on the Health Equity Implementation Framework (HEIF) and the Consolidated Framework for Implementation Research (CFIR). We will develop a codebook based on emerging codes from the transcripts and constructs from HEIF and CFIR. Emerging themes will be summarized highlighting similarities and differences between and within the different groups and SBHCs. Descriptive statistics and chi-square tests of associations will be used to assess the distribution of responses on the assessments between the different sites.DiscussionThis study will describe key implementation determinants and SBIRT-Family adaptation needs from the perspective of multiple end-users. Results will provide insights for a randomized pilot hybrid type 2 effectiveness implementation study of the adapted SBIRT-Family model in two SBHCs assessing effectiveness outcomes (SU and linkage to treatment) and implementation outcomes (reach, adoption, equity, and cost). This research protocol will provide formative data to inform the development of a highly scalable approach that can be used in SBHCs across the country to serve a vulnerable population of adolescents with chronic medical conditions.